2013
DOI: 10.1128/jvi.01301-13
|View full text |Cite
|
Sign up to set email alerts
|

The Genome-Packaging Signal of the Influenza A Virus Genome Comprises a Genome Incorporation Signal and a Genome-Bundling Signal

Abstract: The influenza A virus genome comprises eight single-stranded negative-sense RNA segments (vRNAs). All eight vRNAs are selectively packaged into each progeny virion via so-called segment-specific genome-packaging signal sequences that are located in the noncoding and terminal coding regions of both the 3= and the 5= ends of the vRNAs. However, it remains unclear how these signals ensure that eight different vRNAs are packaged. Here, by using a reverse genetics system, we demonstrated that, in the absence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
84
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 33 publications
1
84
0
Order By: Relevance
“…Taken together, these facts may suggest that nucleotides in the nonconserved NCR play a critical role during virion selective incorporation and that nucleotides in the coding region are mainly responsible for the intersegment interactions. This conclusion is also consistent with a recent proposal that the noncoding region of the NP segment acts as a virion incorporation signal, while the terminal coding region serves as an intersegment bundling signal (26).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Taken together, these facts may suggest that nucleotides in the nonconserved NCR play a critical role during virion selective incorporation and that nucleotides in the coding region are mainly responsible for the intersegment interactions. This conclusion is also consistent with a recent proposal that the noncoding region of the NP segment acts as a virion incorporation signal, while the terminal coding region serves as an intersegment bundling signal (26).…”
Section: Discussionsupporting
confidence: 81%
“…The cis-segment-specific packaging signals for each segment of H1N1 strain WSN or PR8 have been identified experimentally (16)(17)(18)(19)(20)(21)(22)(23)(24)(25), although the precise mechanism is still poorly understood. Recently, it has been proposed that the packaging signal of the NP segment could be divided into two distinct signals, the segment-specific NCR, serving as the incorporation signal, and the terminal coding sequence, serving as the bundling signal (26).…”
mentioning
confidence: 99%
“…However, the underlying mechanism for these observations is still unknown. A study of the NP segment packaging proposed that the NCR serves as an incorporation signal and that the terminal coding sequence serves as the bundling signal (31). Whether the HA segment-specific NCR nucleotides play a role in virus genome bundling needs further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Although early work suggested that the non-coding regions at the extreme termini of each vRNA were the minimal determinants of genome packaging (Luytjes et al, 1989), more recent studies have shown that the extreme 59 and 39 ends of the protein coding regions are required for optimal genome packaging (Hutchinson et al, 2010). These cis-acting sequences are hypothesized to be responsible not only for packaging each genome segment into the virion, but also for forming interactions between segments (Fournier et al, 2012) to create a complex of vRNPs, thereby acting as bundling signals to allow a single copy of each vRNP to be packaged (Goto et al, 2013). It is tempting to speculate that this may be responsible for the '7+1' genome arrangement, which questions whether influenza B viruses contain similar cis-acting packaging sequences due to the significantly different appearance of the vRNPs within the virions.…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrated a genome packaging deficiency in the mutant, and suggested that the deficiency in packaging segment 4 also reduced packaging of other segments. It has been suggested that intermolecular interactions form between influenza A virus vRNPs such that the full complement of vRNPs are present as a complex prior to packaging into virions (Goto et al, 2013). A reduction in packaging efficiency of a single segment could therefore reduce or even prevent packaging of other segments.…”
mentioning
confidence: 99%